DESENTRALISASI DAN GAYA KEPEMIMPINAN SEBAGAI VARIABEL MODERATING DALAM HUBUNGAN ANTARA PARTISIPASI PENYUSUNAN ANGGARAN DAN KINERJA MANAJERIAL - Wahyudin Nor (Universitas Trisakti, 2009)
The relationship between budget participation and managerial performance has been attracting researchers attention. However, the result of previous studies on relationship between budget participation and managerial performance has been often contradictory. One way to reconcile these conflicting result is to investigate the hypothesized relationship utilizing a contingency approach.The purpose of this research is to examine the existing relationship between budget participation and managerial performance. Empirically examined whether decentralisafion and style of leadership are moderating variable that influence the relationship between budget participation and managerial performance. The sample of this research are taken from hybrid public sector organization population in Yogyakarta. From 350 sent questionnaires, there are 112 respondents than send their answer back. Only 101 questionnaires that fulfill the requierements to be processed in final analysis.The empirical result using simple regression show that budget participation influence the managerial performance. But empirically result using residual approach show that a fit between budget participation with contingent factor (decentralisation and style of leadership) does not effect managerial performance significantly.Keywords: Budget participation, Managerial performance, Desentralization, Style of leadership